Countries : their wars and conflicts : a world survey ; Africa - Shally-Jensen, Michael; Salem Press (Ipswich, MA : EBSCO Information Services, Inc.; Amenia, NY : Grey House Publishing, 2019)
Volume 2 of a four volume set that provides an up-to-date overview of conflicts around the globe.
Appendix -- List of Articles by Types of Conflict -- Country Names -- Foreign Embassies in the United States -- International Organizations -- News, Information, and Resources -- World Time Line -- Glossary -- Index.
Salem Press.
Includes bibliographical references and index.
10-A.
Keywords: Since 1900; World politics -- 1989-; Military history, Modern -- 20th century; Military history, Modern -- 21st century; Political violence -- History -- 20th century; Political violence -- History -- 21st century; History